TINJAUAN TERKINI PENANGGULANGAN HIV DI PROVINSI NTB TAHUN 2020 - Alief Defitri; Amanda Agustyaningrum P; Anindhita Qusnul K; Della Oktaveliasari; Dely Silia W; Dira Fanesa; Faranissa Wildania A; Galuh Krisnina F.DM; Ica Mirsa Nuriah (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2024)
HIV and AIDS are very dangerous diseases, and they are a serious concern for the government of the NTB province. The spread of this disease is almost throughout the NTB province. Data from the NTB Provincial Health Office in 2021 shows that the health centers with the highest number of HIV and AIDS cases are among males. This research aims to determine the percentage of the population who died due to HIV/AIDS based on age and gender in the NTB province in 2020. The research method used is a qualitative descriptive research method. Qualitative descriptive research is used to determine the percentage of the population who died due to HIV/AIDS based on age and gender in the NTB province in 2020. Researchers used interviews and documentation. Respondents were selected using purposive random sampling, where the researchers themselves determined who would be the informants for the study. The results of the research show that there are people who are concerned and active in dealing with AIDS, but many are not involved in AIDS prevention due to various factors. Combating AIDS requires active participation from multiple parties, including the government, the community, those who are infected, and those who are affected.